Eating behavior and psychological profile: associations between daughters with distinct eating disorders and their mothers - Verónica Vázquez-Velázquez; Martha Kaufer-Horwitz; Juan Pablo Méndez; Eduardo García-García; Lucy María Reidl-Martínez (BMC, 2017)
Abstract Background Associations of eating behaviors and psychological profile between mothers and daughters with eating disorders exist, but it is important to dissect the influence of the mother in each specific disorder since all eating disorders must be seen or treated not as one entity. The aim of the present study was to evaluate the association of eating behavior and psychological profile between mothers and daughters with different eating disorders and a control group. Methods The study group included young girls with anorexia nervosa (AN, n = 30), bulimia nervosa (BN, n = 30), binge eating disorder (BED, n = 19), and a control group of women (Non-ED, n = 54) together with their mothers. BMI was calculated for dyads and Eating Disorder Inventory, Beck Depression Inventory, Beck Anxiety Inventory, Toronto Alexithymia Scale and Three-Factor Eating Questionnaire were applied. The differences between dyads were tested by Student's t test and Pearson's correlation was used to study the association between BMI, variables of eating behavior and psychological profile in each dyad. Results The study found significant inverse correlations between the AN dyad; some correlations between the BN dyad, and the highest positive correlations exist in BED dyad, especially in eating behavior. Finally, between the control dyads, low but significant correlations were found in the majority of cases. Conclusions The study concluded that the associations between mothers and daughters with distinct eating disorders varied depending on the specific diagnosis of the daughter, indicating it is necessary to analyze them individually, given that there may be different implications for treatment.